СПЕКТР АНТИГЕЛЬМИНТНОЙ АКТИВНОСТИ СУПРАМОЛЕКУЛЯРНОГО КОМПЛЕКСА ФЕНБЕНДАЗОЛА С АРАБИНОГАЛАКТАНОМ - A. I. Varlamova; I. A. Arkhipov (Российский паразитологический журнал, 2019)
Objective of research - to study the biological activity of supramolecular complex of fenbendazole with arabinogalactan against helminthoses of sheep considering spectrum of action. Materials and methods. Anthelmintic activity of supramolecular complex of fenbendazole with arabinogalactan (SMCF) was studied in sheep farms of the Moscow and Samara regions, which were infected with helminthoses. The experiments were made in 2014-2015 in the period of the maximal infection of animals. 386 younger sheep were used in experiments, including 50 sheep spontaneously infected with Dictyocaulus filaria , 48 - Nematodirus spp ., 52 - other gastrointestinal strongylata, 47 - Fasciola hepatica , 49 - Dicrocoelium lanceatum , 42 - Strongyloides sp ., 44 - Trichocephalus spp ., 54 - Moniezia spp . All the animals in each case of helminthoses were divided into 6 equal groups of 7-10 sheep each by the principle of analogs. SMCF was administered orally in the form of 10 % powder at the dose of 1,0; 2,0 and 3,0 mg/kg of active substance once to the sheep of the first, second and third groups. Animals of the fourth and fifth groups received the basic drug - fenbendazole at the doses respectively 1,0 and 7,5 mg/kg of bw except for the cases of fasciolosis and dicroceliasis when SMCF was administered at the doses of 15,0; 7,5 and 5,0 mg/kg and fenbendazole - at the dose of 5,0 and 15,0 mg/kg. The control group did not receive the drug. The efficacy of SMCF was evaluated by the results of larvaovoscopic researches of feces by Berman's method in case of dictyocaulosis, a flotation method in case of other helminthoses before and in 15-18 days after treatment. The efficacy of SMCF was evaluated in «control test» with calculation of middle amount of eggs/larva of helminths in 1 g of feces. Results and discussion. The spectrum of anthelmintic action and the therapeutic dose of SMCF with arabinogalactan, received by mechanochemical technology were studied and defined in experiments on 386 sheep, spontaneously infected with different species of helminths. SMCF showed maximum efficiency (96-100 %) in a dose of 3,0 mg/kg of active substance against main helminthoses and in a dose of 15,0 mg/kg - against dicroceliasis and fasciolosis. The efficacy of SMCF was in 2-3 times higher than activity of fenbendazole substance.